(untitled) (مجلة ديالى للبحوث الانسانية, 2022)
This study aims at investigating the essentially contested concept of immunity which is linguistically used in healthcare marketing posters. It is hypothesized that the concept of immunity is an essential contested concept that fulfilled the seven conditions of Gallie’s model and there is a frequent occurrence due to the concept (Immunity) which is used in healthcare marketing posters. The researchers collect the data from different sources of internet which is concerned with healthcare marketing posters during the Corona Virus period. After analyzing the collected data, the findings have shown that the concept of immunity is an essentially contested concept and met the seventh conditions of Galile’s model , so the concept has received the frequency which is (12) and the frequency and percentage (58%) . Also, using language concepts like immunity as essentially contested concept by users to promote healthcare marketing posters linguistically, so it can be used either to help people in order to strengthen their immunity by taking healthcare products, or to deceive them in order to buy useless products.